Performance Assessment in Islamic Religious Education Learning - Marina Ulfa (International Forum of Researchers and Lecturers, 2025)
In the context of modern education, performance assessment is a crucial instrument for measuring the effectiveness of the learning process. Unlike test-based assessments that generally focus on cognitive aspects, performance assessment highlights students' abilities in applying the knowledge, skills, and attitudes they have learned in various real situations. This is very relevant to the multidimensional characteristics of Islamic Religious Education (PAI) learning, including cognitive (knowledge), affective (attitudes and values), and psychomotor (practice of worship and skills) aspects. This study aims to: 1) To determine the concept and implementation of performance assessment in the context of Islamic Religious Education (PAI) learning. 2) To identify the types of performance assessments that are relevant and can be applied effectively in Islamic Religious Education (PAI) learning. 3) To examine the effectiveness of implementing performance assessments in improving understanding, practice, and character building. This study uses a qualitative approach with the model used being library research. The results of the study indicate that performance assessment in Islamic Religious Education (PAI) learning is a form of authentic evaluation that is very important to be applied in the learning process. Unlike traditional assessments, which emphasize cognitive aspects, performance assessments provide balanced attention to cognitive, affective, and psychomotor aspects. These assessments assess not only what students know, but also who they become. Therefore, it is crucial for teachers and educational institutions to optimally integrate performance assessments to shape a generation that is not only intellectually intelligent but also spiritually and socially mature.